Theoretical schools on employment and workforce - Béresné Mártha, Bernadett (Acta Agraria Debreceniensis, 2009)
In the civil economics, like in the case of any other socialeconomic issues, there are two coexistent theories concerning employment. On one hand we have the classical-neo-classicalschool based on Adam Smith’s works. On the other hand we have the teachings based on John Maynard Keynes’ views. All the later hypotheses are based on these two trends.Monetarism, which was invented at the beginning of the 20th century, mixes certain elements of both basic theories. Those who represent monetarism agree on rejecting the economy policymeans which affect the processes of the workforce market, while they consider these above mentioned means applicable to regulate certain processes. By the end of the 1970s the neo-classical macro-economics had developed, which completely refuses these approaches. A decade later the neo-Keynesian macro-economics developed. Its hypotheses regarding  especially employment and unemployment lead to some of the employment issues of globalism, which is one of the most influential phenomena of present time.